Lung function in African infants in the Drakenstein child health study impact of lower respiratory tract illness - Gray, D.; Turkovic, L.; Willemse, L.; Visagie, A.; Vanker, A.; Stein, D.; Sly, P.; Hall, Graham; Zar, H. (American Thoracic Society, 2017)
Rationale: Lower respiratory tract illness is a major cause of childhood morbidity and mortality. It is unknown whether infants are predisposed to illness because of impaired lung function or whether respiratory illness reduces lung function. Objectives: To investigate the impact of early life exposures, including lower respiratory tract illness, on lung function during infancy. Methods: Infants enrolled in the Drakenstein child health study had lung function at 6 weeks and 1 year. Testing during quiet natural sleep included tidal breathing, exhaled nitric oxide, and multiple breath washout measures. Risk factors for impaired lung health were collected longitudinally. Lower respiratory tract illness surveillance was performed and any episode investigated. Measurements and Main Results: Lung function was tested in 648 children at 1 year. One hundred and fifty (29%) infants had a lower respiratory tract illness during the first year of life. Lower respiratory tract illness was independently associated with increased respiratory rate (4%; 95% confidence interval [CI] , 1.01-1.08; P = 0.02). Repeat episodes further increased respiratory rate (3%; 95% CI, 1.01-1.05; P = 0.004), decreased tidal volume (21.7 ml; 95% CI, 23.3 to 20.2; P = 0.03), and increased the lung clearance index (0.13 turnovers; 95% CI, 0.04-0.22; P = 0.006) compared with infants without illness. Tobacco smoke exposure, lung function at 6 weeks, infant growth, and prematurity were other independent predictors of lung function at 1 year. Conclusions: Early life lower respiratory tract illness impairs lung function at 1 year, independent of baseline lung function. Preventing early life lower respiratory tract illness is important to optimize lung function and promote respiratory health in childhood.